DENSIDADE DE PLANTAS E USO DE FUNGICIDA NA OCORRÊNCIA DE DOENÇAS FOLIARES E NA PRODUTIVIDADE DE BULBOS DE CEBOLA - Harms, Mônica Gabrielle (2013)
The ideal plants density consists in an extremely important condition in the determining of yield and in the commercial production of onion bulbs. The producers have sought new spatial distributions of plants, aiming harvest bulbs in accord with the size required by the consumer. The plants population have also influence on the development of diseases, because it is associated with the infective units spread of the pathogen and microclimate in culture. The experiment was conducted in the Capão da Onça School Farm aiming to evaluate the influence of plants density and the fungicide use in the occurrence of foliar diseases and the productive characteristics of Bola Precoce cultivar and Bella Dura hybrid. The experimental design was complete randomized blocks, with four replications for the Bola Precoce cultivar and three replications for the Bella Dura hybrid. The treatments were arranged in a split plot design, where the plots were either the presence or the absence of fungicide (metiram + piraclostrobina - 2,5 kg p.c. ha-1) and plant densities (12, 14, 16, 18, 20 and 22 plants m-1) were the split plots. Parameters evaluated were: severity of downy mildew (Peronospora destructor) and purple blotch (Alternaria porri), number of harvest bulbs, bulb mass, bulb diameter, bulb classification and yield. With the data of severity, the area under disease progress curve (AUDPC) was calculated. For Bola Precoce cultivar, no differences were observed between the densities for the parameters AUDPC (downy mildew and purple blotch), purple blotch severity, bulb mass, bulb diameter and bulbs class 0, 2, 3 and 3C. There was difference between densities for downy mildew severity in the evaluation made at 111 days after transplantation (DAT), and the maximum value (34,65%) was found in 15,3 plants m-1 density, in presence of fungicide. The fungicide was effective on downy mildew control in the evaluation made at 97 DAT and on the purple blotch control in the evaluation made at 97 and 104 DAT. The maximum yield was obtained in 22 plants m-1 density, reaching 18,21 and 17,70 t ha-1 in presence and absence of fungicide, respectively. For Bella Dura hybrid, no differences were observed between densities for AUDPC (downy mildew and purple blotch), bulbs class 0, downy mildew severity at 90, 97 and 104 DAT, and purple blotch severity at 90, 97 and 111 DAT. The fungicide was effective in controlling downy mildew in the evaluations made at 97 and 104 DAT. In absence of fungicide, the yield increased with the plant density increasing. In presence of fungicide, the maximum yield (22,09 t ha-1) was obtained in 17,45 plants m-1 density. There was a reduction of the mass and diameter of bulb with the plant density increment, when no fungicide was applied. In presence of fungicide, the percentage of bulbs class 3C decreased with the plant density increase.